CGRP receptor blockade by MK‐8825 alleviates allodynia in infraorbital nerve‐ligated rats. (5th November 2014) - Michot, B.; Kayser, V.; Hamon, M.; Bourgoin, S.
Abstract Background Previous data showed that, in rats, anti‐migraine drugs (triptans, olcegepant) significantly reduced mechanical allodynia induced by infraorbital nerve (ION) ligation but not that evoked by sciatic nerve (SN) ligation. Whether this also occurs with MK‐8825, a novel anti‐migraine drug also acting through CGRP receptor blockade (but chemically unrelated to olcegepant) was tested in the present study, which also investigated possible anti‐neuroinflammatory effects of this drug. Methods Adult male Sprague‐Dawley rats underwent unilateral chronic constriction injury (CCI) to either the ION or the SN, and mechanical allodynia was assessed 2 weeks later within the ipsilateral vibrissae territory or hindpaw, respectively. Transcripts of neuroinflammatory markers were quantified by real‐time quantitative RT‐PCR in ipsilateral trigeminal ganglion and spinal trigeminal nucleus in CCI‐ION rats. Results Acute as well as repeated (for 4 days) administration of MK‐8825 (30–100 mg/kg, i.p.) significantly reduced CCI‐ION‐induced mechanical allodynia but was ineffective in CCI‐SN rats. CCI‐ION was associated with marked up‐regulation of neuronal and glial inflammatory markers (ATF3, IL6, iNOS, COX2) in ipsilateral trigeminal ganglion but not spinal trigeminal nucleus. MK‐8825‐induced inhibition of iNOS mRNA up‐regulation probably underlay its anti‐allodynic effect because pharmacological blockade of iNOS by AMT (6 mg/kg, s.c.) mimicked this effect. Conclusions These data further support the idea that CGRP receptor blockade might be a valuable approach to alleviate trigeminal, but not spinal, neuropathic pain through, at least partly, an inhibitory effect on neuropathic pain‐associated increase in NO production in trigeminal ganglion.